Understanding civil wars : continuity and change in intrastate conflict - Newman, Edward 1970- (London : New York : Routledge, 2014)
"This volume explores the nature of civil war in the modern world and in historical perspective. Civil wars represent the principal form of armed conflict since the end of the Second World War, and certainly in the contemporary era. The nature and impact of civil wars suggests that these conflicts reflect and are also a driving force for major societal change. In this sense, Understanding Civil War: Continuity and Change in Intrastate Conflict argues that the nature of civil war is not fundamentally changing in nature. The book includes a thorough consideration of patterns and types of intrastate conflict and debates relating to the causes, impact, and 'changing nature' of war. A key focus is on the political and social driving forces of such conflict and its societal meanings, significance and consequences. The author also explores methodological and epistemological challenges related to studying and understanding intrastate war. A range of questions and debates are addressed. What is the current knowledge regarding the causes and nature of armed intrastate conflict? Is it possible to produce general, cross-national theories on civil war which have broad explanatory relevance? Is the concept of 'civil wars' empirically meaningful in an era of globalization and transnational war? Has intrastate conflict fundamentally changed in nature? Are there historical patterns in different types of intrastate conflict? What are the most interesting methodological trends and debates in the study of armed intrastate conflict? How are narratives about the causes and nature of civil wars constructed around ideas such as ethnic conflict, separatist conflict and resource conflict? This book will be of much interest to students of civil wars, intrastate conflict, security studies and IR in general"--
Introduction -- Scholarship on civil war : topics, debates and controversies -- Framing civil war studies -- Japan 1877 -- The American Civil War 1861-65 -- Liberia 1989-96 -- Bosnia 1992-95 -- Sri Lanka 1983-2009 -- Patterns of civil war in historical perspective -- Civil Wars in the 21st century : new wars, declining wars and post-colonial wars of statebuilding -- Containing, ending and resolving civil war.
Includes bibliographical references and index.
Keywords: Civil war; Civil war -- Social aspects; War (International law); HISTORY / Military / United States; HISTORY / Military / Strategy; POLITICAL SCIENCE / Political Freedom & Security / International Security